Pembatasan Terhadap Hak-Hak Perempuan Oleh Taliban Perspektif Convention On The Elimination Of All Forms Of Discrimination Against Women - Nur Reski Molle; Irma Halimah Hanafi; Popi Tuhulele (Faculty of Law, Universitas Pattimura, 2023)
Introduction: This research discusses about about restrictions on women's rights by the taliban perspective convention on the elimination of all forms of discrimination against women (CEDAW) 1979 relating to cases of discrimination against women by the Taliban in Afghanistan. The Taliban restricts women's rights leading to discrimination against women.Purposes of the Research: This study aims to restore the rights of women who are restricted by the Taliban related to women's rights convention on the elimination of all froms of discrimination against women (CEDAW) 1979. Methods of the Research: This research uses the juridical normative method by using a statutory approach, a conceptual approach, and a case approach.Results of the Research: from the writings of the Taliban who have controlled Afghanistan, the Taliban have restricted women's rights. The rights of women that are limited by the Taliban are the right to get decent work and education. In convention on the alimination of all forms of discrimination against women (CEDAW) 1979 Article 10 regulates education and article 11 regulates employment.